2019
DOI: 10.3389/fimmu.2019.01703
|View full text |Cite
|
Sign up to set email alerts
|

Does Natural Killer Cell Deficiency (NKD) Increase the Risk of Cancer? NKD May Increase the Risk of Some Virus Induced Cancer

Abstract: Natural killer cell deficiency (NKD) is a primary immunodeficiency where the main defect lies in CD56 + CD3 − natural killer (NK) cells which mediate cytotoxicity against tumors. Most cases are observed in children and adolescents with recurrent viral infections and cancer. GATA2 and MCM4 mutations are found in NKD patients with cancer. However, the question remains unclear whether NKD increases the risk of cancer. Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
0
28
2
Order By: Relevance
“…As in our patient, low NK cell counts are found in up to 33% of post-transplant patients, and may further contribute to HPV susceptibility (22). Defects in NK cell function also increase risk of viral induced cancers (23,24). HPV infection, including genital warts, and poor NK killing in our patient put him at high risk for squamous cell carcinoma, highlighting the need for continued monitoring.…”
Section: Discussionmentioning
confidence: 51%
“…As in our patient, low NK cell counts are found in up to 33% of post-transplant patients, and may further contribute to HPV susceptibility (22). Defects in NK cell function also increase risk of viral induced cancers (23,24). HPV infection, including genital warts, and poor NK killing in our patient put him at high risk for squamous cell carcinoma, highlighting the need for continued monitoring.…”
Section: Discussionmentioning
confidence: 51%
“…I have also evaluated patients, upon request, who have had incidental laboratory findings have been obtained, and ultimately the only unifying theme I have been able to identify where NK cells are truly deficient is that of where patients have clinical susceptibility herpesviruses and some warts. I am not presently aware of enough signal to attribute cancer susceptibility to NKD but remain concerned and would refer the reader to a recent overview [47].…”
Section: What Is Nkdmentioning
confidence: 99%
“…In theory, NKD could present an increased risk for malignancy and there have been a few identified in individuals with NKD, particularly EBV-driven [59,60] and HPV-driven [31] cancers and as such most reported appear to be virally-driven. An overview of these concerns has been reviewed and commented upon by others [47]. For now, the malignancy risk is more theoretical, and as NKD patients are collected and followed for prolonged periods more clarity will be obtained.…”
Section: Getting the Nkd Diagnosis Right And The Index Of Suspicionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different activating receptors on the surface of NK cells comprising: Natural killer receptors (NCRs), NKG2D, and CD16 (FcγRIII) (2,3). It is shown that decreased activity of peripheral blood lymphocyte specially NK cells is associated with higher cancer risk (4)(5)(6). Of note, the inhibitory effect of the tumor microenvironment might also decline the effector functioning of the NK cells by downregulation of activating receptors such as NCRs (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%